PENGEMBANGAN MEDIA E-BOOK INTERAKTIF PADA MATERI STRUKTUR DAN FUNGSI JARINGAN ORGAN TUMBUHAN - ASTRINI WIDYANITA (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2012)
Abstract: The aims of this research are 1) produce interactive e-book media as a learning media, 2) describe the properness of the improved interactive e-book media. The phases of this research are preparation phase, media creation phase, and limited try out phase to fifteen 3rd grade students of Muhammadiyah 4 senior high school Surabaya. The result of this research showed that the improved interactive e-book media is proper. This result was shown from the research of competent lecturers and biology teachers that included media format aspect, music aspect, subject aspect, video aspect, self evaluation aspect, a 100% for each aspect. The student response result toward the improved e-book media showed an average of 94%. Keywords: Interactive e-Book Media, structure and function of plant tissue organ, improvemental research.